Synthesis and Structure of a Tetraazamacrocyclic Complex [NiL·Zn(SCN)4] - Xia, Hong; Huang, Zi-Xian; Bi, Jian-Hong (Asian Journal of Chemistry, 2010)
The complex [NiL·Zn(SCN)4] ( L = 5,5,7,12,12,14-hexa-methyl-1,4,8,11-tetraazamacrocyclic- 4,11-diene) was synthesized and characterized by IR spectra and elemental analysis and the structure was determined by single-crystal X-ray diffraction analysis. The result showed the crystal belongs to monoclinic, space group P2(1)/n with a = 11.842(3) Å, b = 14.835(3) Å, c = 16.463(4) Å, a = 90º, b = 92.087(4)º, g = 90º, V = 2890.0(11)Å3, Z = 4, Dc = 1.464 Mg/cm3, F(000) = 1320, R = 0.0497, wR = 0.1326. In the crystal, Ni(II) ion was coordinated by four nitrogen atoms of the tetraazamacrocycle.